2013
DOI: 10.1002/aenm.201300181
|View full text |Cite
|
Sign up to set email alerts
|

A Solution‐Processable Small Molecule Based on Benzodithiophene and Diketopyrrolopyrrole for High‐Performance Organic Solar Cells

Abstract: A linear solution‐processable small molecule (BDT‐2DPP) based on 5‐alkylthiophene‐2‐yl‐substituted benzodithiophene and diketopyrrolopyrrole is designed and synthesized. BDT‐2DPP exhibits strong and broad absorption with low band gap, low lying energy levels matching with PC61BM and high hole mobility. Solution‐processed organic solar cells based on BDT‐2DPP:PC61BM blend showed power conversion efficiencies as high as 5.79%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
144
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(148 citation statements)
references
References 47 publications
3
144
1
Order By: Relevance
“…13 C NMR spectra were recorded on a Bruker DRX500 at a frequency of 125 MHz. In the case of 1 H NMR spectroscopy, the compounds to be analysed were taken in the form of 1% solutions in CDCl 3 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…13 C NMR spectra were recorded on a Bruker DRX500 at a frequency of 125 MHz. In the case of 1 H NMR spectroscopy, the compounds to be analysed were taken in the form of 1% solutions in CDCl 3 .…”
Section: Methodsmentioning
confidence: 99%
“…In the case of 1 H NMR spectroscopy, the compounds to be analysed were taken in the form of 1% solutions in CDCl 3 . In the case of 13 C NMR spectroscopy, the compounds to be analysed were taken in the form of 5% solutions in CDCl 3 . The spectra were then processed on the computer using the ACD Labs soware.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Devices employing solution-processed small molecules as both donor and acceptor components gave device efficiencies of $3%, 18 which is similar to the average device performance of the widely studied and extensively optimized polymer : fullerene P3HT : PC60BM system. 19 As a result of this progress, a wide variety of new small molecules for solutionprocessed organic photovoltaics are being prepared, [20][21][22][23][24] including efficient donor-acceptor-donor (D-A-D) systems. 25 A recent electrochemical study of non-oxidised 4H-1,2,6-thiadiazines indicated electron affinities (LUMO energy values) of À3.25 to À3.66 eV with reversible oxidations and reductions.…”
Section: Introductionmentioning
confidence: 99%